Diagnostic value of pyroninophilic lymphocyte in dengue haemorrhage fever in children - Setya Wandita, Setya Wandita (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Dengue hemorrhagic fever (DHF) is still a problem in Indonesia. Early diagnosis is important in the management. The cytoplasm of activated lymphocytes in dengue infection contains ribonucleic acid (RNA). RNA can be specifically shown by pyronin staining.Objective: To know the diagnostic value of lymphocyte pyroninophilic in DHF in children.Methods: Subjects were patients hospitalized in the Pediatric Department of Faculty of Medicine/Pediatric Ward Sardjito General Hospital, from September 1995 to December 1996, with 2-7 days of fever, positive tourniquet test, and 0-14 years of age. Clinical diagnosis of DHF was based on WHO 1986 criteria. Hemagglutination inhibition (HI) test and/or antibody antidengue were used to confirm the diagnosis of DHF. Peripheral blood smear was stained with pyronin stain according to Sutaryo modification. Lymphocyte percentage was counted per 100 leukocyte under light microscope.Results: Means of pyroninophilic lymphocyte numbers were increased from day-3 to day-5 of fever and then decreased. There were significant difference between the means in non-dengue infection and in dengue infection from day-3 to day-7 of fever, between dengue fever (DF) and DHF from day-3 to day-6 of fever, and between non shock (DHF-I and DHF-II) and shock cases (DHF-III and DHF-IV) from day-3 to day-9 of fever. The number of pyroninophilic lymphocytes correlated with the degree of DHF. Using cut-off point of 4 at day-5 of fever, the sensitivity was 86,2%, specificity was 84,3%, positiv predictive value was 92,6%, and negative predictive value was 65,1%.Conclusion: Pyroninophilic lymphocyte has a high diagnostic value in DHF in children.Key words: Dengue hemorrhage fever - ribonucleic acid - pyroninophilic lymphocyte - diagnosis